Влияние микроволнового излучения на температурные особенности обезвоживания - Рыщенко, Игорь Михайлович; Русинов, Александр Иванович; Блинков, Николай Андреевич (НПП ЧП "Технологический Центр", 2015)
Применением микроволнового облучения удалось добиться более эффективной регенерации неорганических солей-кристаллогидратов, понизить температуру ее начала, а также установить строение кристаллизационной воды и сравнить ее с прототипами – фазовыми модификациями льда. Также удалось установить, что применение микроволнового излучения может быть полезным при замене традиционного способа регенерации кристаллогидратов с применением высокой температуры.

In crystal hydrates of inorganic salts, water is in a particular, bound state. The crystal lattice of each crystal hydrate is individual, and by default it should be similar to the structure of the water ice Ih, which is not observed in practice. It is assumed that the water of crystallization with the crystal hydrate is frozen water in other forms of ice that correspond to specific phases of ice, and salt simulates the application of high pressure. Due to the study of weight loss, the assumption is confirmed. Using microwave radiation also allows to reduce the adsorbent recovery temperature, which is very important for lower energy expenditure. So, many crystal hydrates are melted in the water of crystallization, which makes it necessary to evaporate water from it, and can also fill in the recovery installation. Microwave radiation is weakly absorbed directly by ice because of the symmetry in it, and weak intermolecular vibration, in depth, and, therefore, it starts from the surface. The appearance of the salt in the water of crystallization can also be presented in the form of ice, and this significantly improves the absorptivity and allows the water of crystallization to volatilize, which provides recovery. Thus, using a microwave oven as an alternative method of recovery is highly relevant.
Influence of microwave radiation on temperature characteristics of dehydration
Keywords: кристаллогидраты; регенерация; лед; фаза; решетка; давление; температура; crystal hydrates; radiation; recovery; ice; phase; lattice; pressure; temperature